Screening of micromycete strains that are promising for crop growth promotion (Experimental biology, 2020)
One of the current trends in the development of sustainable agriculture is the microbial biotechnology, contributing to the greening of agricultural production. Microorganisms are able to promote the growth and development of plants through various direct and indirect mechanisms. The interest in such microorganisms is associated with the possibility of using them to increase the yield of agricultural crops, improve the quality of agricultural products, restore soil fertility, etc. In the present study we examined the biotechnologically valuable properties of 848 micromycete strains (653 filamentous fungi and 195 yeasts) isolated from the agrocenoses of grain, forage and oilseeds of Kazakhstan. The strains capable of producing phyothhormones auxins and hydrolytic enzymes, the isolates with phosphate-mobilizing ability, cellulolytic and antagonistic activities, as well as tolerant to heavy metals, were  identified. As a result of the screening, 44 strains that demonstrated the highest activity and possess several valuable properties were selected. Seed pre-treatment with these strains (in 35 cases out of 45) led to the promoting effect expressed in enhancing seed germination and increasing morphometric parameters of 14-day-old barley seedlings. As a result, 35 strains were selected for further detailed study of their properties and the possibility of application them for crop growth promotion.Key words: micromycetes, plant growth promoting activity, phyothhormones, phosphate-mobilization, antagonism